Use of Video Tutorials in the Learning Process of University students - María del Socorro Rodríguez Guardado; Alejandra Platas-García (Universidad Autónoma de Baja California, 2022)
The objective of this study is to explore the effect of prior experience (PE) and intrinsic motivation (IM) on the perception of learning (PL) of university students when they use online video tutorials. The methodology follows a quantitative, non-experimental, correlational, and cross-sectional research design, applying the Technology Acceptance Model (TAM) to 112 university students from different institutions and academic programs. The results from the first phase of the study show that YouTube is the platform most commonly used by students to search for video tutorials to help them academically, while the second phase reveals a positive correlation between PE and IM (rs= 0.526; p< 0.01) and between IM and PL (rs= .492; p< 0.01). These results indicate that video tutorials are a valuable tool that boosts students' motivation in their learning process.